2016
DOI: 10.1016/j.optom.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ocular biometry and anterior chamber parameters after pharmacologic mydriasis and peripheral iridotomy in primary angle closure suspects

Abstract: PurposeThe aim of this study was to evaluate the effects of pharmacologic mydriasis and Peripheral Iridotomy (PI) on ocular biometry and anterior chamber parameters in primary angle closure suspects.MethodsIn this prospective interventional case series, 21 primary angle closure suspects were enrolled. Intraocular pressure, refraction, ocular biometry (Lenstar, LS900), and anterior chamber parameters (Pentacam HR) were measured at four occasions: before PI (before and after mydriasis with phenylephrine) and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…[8] The lack of any changes in the ocular biometric parameters in our patients of both groups is in line with other studies on the angle closure patients. [24,25,26,27] In a group of fellow eyes of 21 patients with acute primary angle closure and in 17 patients with PACG, the ACD did not change following WDT. [26] The study by Poon et al on PACG and primary open-angle glaucoma revealed no association between WDT-IOP changes and anterior chamber depth and axial length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] The lack of any changes in the ocular biometric parameters in our patients of both groups is in line with other studies on the angle closure patients. [24,25,26,27] In a group of fellow eyes of 21 patients with acute primary angle closure and in 17 patients with PACG, the ACD did not change following WDT. [26] The study by Poon et al on PACG and primary open-angle glaucoma revealed no association between WDT-IOP changes and anterior chamber depth and axial length.…”
Section: Discussionmentioning
confidence: 99%
“…[27] In a study on PACS patients, no changes in ocular biometric or anterior chamber parameters including iridocorneal angle after peripheral iridotomy and/or pharmacologic mydriasis except for increments in anterior chamber volume were observed. [24]…”
Section: Discussionmentioning
confidence: 99%
“…Also, another study was done by Razeghinejad et al (29) showed that the mydriatic test didn't cause a signi cant difference in intraocular pressure or parameters of anterior chamber except the anterior chamber volume, which increased after the mydriatic test. Our study differs from this one in many aspects, rstly, in ours, there was a signi cant increase in IOP measurements after mydriasis, secondly, this study revealed a signi cant increase in ACV post mydriatic while ours showed a non-signi cant decrease in ACV post mydriatic…”
Section: -As-oct Parametersmentioning
confidence: 98%